Numerical Simulation and Process Optimization of Laser Welding in 6056 Aluminum Alloy T-Joints - Jin Peng; Shihua Xie; Tiejun Chen; Xingxing Wang; Xiaokai Yu; Luqiang Yang; Zenglei Ni; Zicheng Ling; Zhipeng Yuan; Jianjun Shi; Zhibin Yang (Crystals)
This paper conducts a numerical simulation of the laser welding process for 6056 aluminum alloy stringers and skin T-joints using Simufact Welding. Initially, the accuracy of the finite element simulation is validated, followed by an exploration of the impact of bilateral asynchronous and bilateral synchronous laser welding on molten pool stability. Process parameters, including laser power, welding speed, fixture clamping force, and preheat temperature, are optimized through orthogonal testing. Furthermore, the influence of welding sequences on post-weld equivalent stress and deformation in three stringers’ T-joints is analyzed. The numerical simulation results indicate that the stability of the molten pool is superior in bilateral synchronous welding compared to asynchronous welding. Optimized process parameters were obtained through orthogonal testing, and subsequent experiments demonstrated that the welding sequence of welding both sides first, followed by the middle, produced lower post-weld equivalent stress and reduced overall joint deformation.